Italian Validation of the Capacity to Love Inventory: Preliminary Results - Margherita, Giorgia; Gargiulo, Anna; Troisi, Gina; Tessitore, Francesca; Kapusta, Nestor D. (Frontiers in Psychology, 2018)
Introduction: Within a wider international research project aimed at operationalize the psychodynamic construct of capacity to love (Kernberg, 2011), the Capacity to Love Inventory (CTL-I) is a 41-items self-report questionnaire assessing six dimensions: interest in the life project of the other, basic trust, gratitude, common ego ideal, permanence of sexual passion, loss and mourning. Objectives: The study is aimed at validating the Italian version of the CTL-I. Method: A total sample of 736 Italian non-clinical adults was administered a checklist assessing socio-demographic variables, and the CTL-I. AConfirmatory Factor Analyses (CFA) was conducted to examine the construct validity of the Italian version of the CTL-I. Only a part of the total sample (320 participants) was administered an additional series of concurrent measures in order to investigate the convergent validity of the CTL-I. Correlations with measures of socio-sexual orientation, quality of romance relations, and psychopathological questionnaires were examined through Pearson’s correlation coefficients. Results: CFA results suggested that the Italian CTL-I fully replicated the six-factor structure of the original CTL-I. Cronbach’s alpha index provided satisfactory results for all subscales and the correlations with concurrent measures were in expected direction. Conclusion: The results showed promising psychometric characteristics of the Italian version of CTL-I. Implications of the feasibility of the instrument in clinical and psychotherapeutic settings are discussed.